Perception of Telemedicine and Digital Healthcare in Kathmandu Valley - Shrestha, Raji (International Journal of Atharva, 2026)
Background: Telemedicine and digital medicine have been developed as revolutionary tools for improving access to healthcare facilities especially in areas where there is geographic and infrastructural difficulty. Nepal stands at a unique position with respect to the delivery of health care services due to its challenging geography and rural environment. Despite efforts by the Nepalese government to develop the Digital Nepal Strategy (2019), inconsistency prevails regarding telemedicine applications. Methods: A descriptive cross-sectional research design was adopted through an online survey conducted on 206 Nepalese citizens aged 18 and above. The data were collected from a structured questionnaire assessing awareness, perceptions related to environmental sustainability, accessibility, trust, and telemedicine. Analysis of the results was done through SPSS. Results: Most participants belonged to the age group 18-25 (52.9%), while males made up 51.9% and females 48.1%. There were more urban respondents, making 56.8% of all participants. Awareness level was found significantly higher than neutral point (M=3.46, t=7.640, p<.001). Respondents saw the contribution of telemedicine towards environmental sustainability (M=3.45, t=8.937, p<.001) and improvement in rural healthcare services access (M=3.36, t=4.556, p<.001). Internet connectivity was indicated as one of the most important barriers (M=3.52, t=6.795, p<.001). Trust towards telemedicine was higher regarding minor illnesses (M=3.37, t=4.493, p<.001), while it increased with governmental regulation (M=3.48, t=6.292, p<.001). Finally, adoption rate was positively correlated with awareness level (r=0.309, p<.01) and environmental perception (r=0.425, p<.01). Conclusion: The perceptions held by the Nepalese population towards telemedicine are largely positive as the use of technology is seen to have the potential of improving health accessibility and the environment. Nonetheless, issues such as internet availability and lack of emergency care need to be considered. Governmental regulation became a key factor to gain trust. These results can help policymakers create an efficient digital health approach based on the evidence. Novelty: The current study provides empirical evidence concerning telemedicine perceptions in terms of awareness, environmental sustainability, accessibility, trust, and adoption.